2000
DOI: 10.1128/jcm.38.12.4511-4516.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-Acquired, Autochthonous Human Babesiosis in Japan: Isolation of Babesia microti -Like Parasites with hu-RBC-SCID Mice

Abstract: We have isolated piroplasms from a patient who developed the first case of human babesiosis in Japan by using NOD/shi-scidmice whose circulating erythrocytes (RBCs) had been replaced with human RBCs (hu-RBC-SCID mice). Following inoculation of the patient's blood specimen into hu-RBC-SCID mice, parasites proliferated within the human RBCs in the mice, resulting in a high level of parasitemia. Parasite DNA was prepared from blood samples of the patient and the mice, and the nuclear small-subunit rRNA gene (rDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…Nevertheless, individuals returning to the U.S. from combat zones in Iraq are currently deferred for one year. Aside from parasites, other tick-borne agents such as the two bacteria Anaplasma phagocytophilum and Rickettsia rickettsii have been rarely found in blood products although most TT tick-borne infections have been largely confined to the Northeastern U.S. and one case of TT babesia infection in Japan [116,117].…”
Section: Parasitesmentioning
confidence: 99%
“…Nevertheless, individuals returning to the U.S. from combat zones in Iraq are currently deferred for one year. Aside from parasites, other tick-borne agents such as the two bacteria Anaplasma phagocytophilum and Rickettsia rickettsii have been rarely found in blood products although most TT tick-borne infections have been largely confined to the Northeastern U.S. and one case of TT babesia infection in Japan [116,117].…”
Section: Parasitesmentioning
confidence: 99%
“…Previous studies reported that serum samples from an individual infected with a Kobe lineage organism showed strong reactivity to the Kobe lineage, but weak reactivity to the US and Hobetsu lineages. 17,21 Taken together, these observations indicate that B. microti antibody reacted specifically to homologous antigens among the sublineages of B. microti. Indirect immunofluorescence assay is a method used generally for antibody detection in human babesiosis around the world.…”
Section: Discussionmentioning
confidence: 64%
“…14 Kobe524 (Kobe lineage) was isolated from a blood sample of a TTB patient in Japan. 17,24 Ho234 (Hobetsu lineage) was isolated from a rodent in Japan. 21 The lineages and sublineages of the US lineage of the B. microti strains used were previously determined by phylogenetic analysis based on the sequences of B. microti 18S rRNA, b-tubulin, and CCTeta genes.…”
Section: B Microtimentioning
confidence: 99%
See 2 more Smart Citations